2018
DOI: 10.1186/s12886-018-0742-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of number and position of intraocular lens haptics on anterior capsule contraction: a randomized, prospective trial

Abstract: BackgroundThe present study aimed to evaluate the degree of anterior capsule contraction (capsulorhexis contraction) with three different single-piece, hydrophilic acrylic intraocular lenses (IOLs).MethodsPatients were prospectively randomized to be implanted with one of three types of IOLs during cataract surgery: the Ophtec Precizon (IOL A), the Lucid Korea Microflex (IOL B), and the Carl Zeiss Asphina (IOL C). One week, 2 weeks, and 6 months after surgery, the area of the anterior capsule opening was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 29 publications
1
32
0
4
Order By: Relevance
“…Kim et al reported a contraction in the anterior capsule of 18.60-18.99 mm 2 on average during surgery to 16.81-17.75 mm 2 in the 3month observation period for cataract surgery patients who had an intraocular lens implanted, similar to the ones used in the current study. Overall, the average reduction in the capsulorrhexis field formed 6.76-10.87 % of the size of the initial capsulorrhexis in eyes without pathology (Kim et al, 2013), and similar tendencies in eyes without pathology corresponded to the observations made by Choi et al (Choi et al, 2018) and Corydon et al (Corydon et al, 2007). Whereas, as reported by Kato, contraction of the capsulorrhexis in a 9-month period, reduces by 14 % on average in eyes without pathology (Satoshi Kato et al, 2002).…”
Section: Shah Et Al Reported About 59 Cases Of Traumatic Subluxated Lenses In Larkanasupporting
confidence: 75%
See 1 more Smart Citation
“…Kim et al reported a contraction in the anterior capsule of 18.60-18.99 mm 2 on average during surgery to 16.81-17.75 mm 2 in the 3month observation period for cataract surgery patients who had an intraocular lens implanted, similar to the ones used in the current study. Overall, the average reduction in the capsulorrhexis field formed 6.76-10.87 % of the size of the initial capsulorrhexis in eyes without pathology (Kim et al, 2013), and similar tendencies in eyes without pathology corresponded to the observations made by Choi et al (Choi et al, 2018) and Corydon et al (Corydon et al, 2007). Whereas, as reported by Kato, contraction of the capsulorrhexis in a 9-month period, reduces by 14 % on average in eyes without pathology (Satoshi Kato et al, 2002).…”
Section: Shah Et Al Reported About 59 Cases Of Traumatic Subluxated Lenses In Larkanasupporting
confidence: 75%
“…The average capsulorrhexis area for research patients was 14.24 mm 2 during surgery, which is markedly smaller than the usual capsulorrhexis area created during an uncomplicated cataract operation, which is usually 5-5.5 mm (Choi et al, 2018;Hayashi et al, 2011;Hayashi & Hayashi, 2005;Kim et al, 2013) in diameter, corresponding to 19.625-23.75 mm 2 area. A small capsulorrhexis area for research patients can be explained by 2 factors -pronounced lens mobility due to weakened or non-existing zonules Vasavada et al, 2012b) and the surgical technique used in which the iris or capsular hooks (retractors) are attached to the capsulorrhexis (and consequently, the entire lens) edge.…”
Section: Shah Et Al Reported About 59 Cases Of Traumatic Subluxated Lenses In Larkanamentioning
confidence: 83%
“…The average capsulorrhexis area for research patients was 14.3 mm 2 during surgery, which is markedly smaller than the usual capsulorrhexis area created during an uncomplicated cataract operation, which is usually 5–5.5 mm [ 32 , 33 , 34 , 35 ] in diameter, corresponding to a 19.625–23.75 mm 2 area. A small capsulorrhexis area for research patients can be explained by two factors—pronounced lens mobility due to weakened or non-existing zonules [ 28 , 31 ] and the surgical technique used in which the iris or capsular hooks (retractors) are attached to the capsulorrhexis (and consequently, the entire lens) edge.…”
Section: Discussionmentioning
confidence: 89%
“…The surgeries were performed with phacoemulsification and IOL implantation in the capsular bag. Small initial capsulorhexis (anterior capsule openings), if compared to other published data [ 32 , 33 , 34 , 35 ], were created due to the weak zonules.…”
Section: Methodsmentioning
confidence: 87%
“…[27] In addition, the IOL haptic design and material were reported to have effects on LECs proliferation and capsule contraction. [28,29] Both the implantation and location of IOL played important roles in anterior capsule stability and migration of LECs. After lens removed, the remnant LECs on the capsular bag underwent proliferation and transdifferentiation, resulting in capsule opacification.…”
Section: Discussionmentioning
confidence: 99%